Microbial biofilms in bioremediation and wastewater treatment - Nancharaiah, Y. V. 1970-; Venugopalan, Vayalam P. (CRC Press, 2019)
"Biofilms represent the natural living style of microbial communities and plays a pivotal role in biogeochemical cycles and natural attenuation. Biofilms can be engineered for biodegradation and biotransformation of organic and inorganic contaminants, for both in situ bioremediation and ex situ treatment in bioreactors. This book focuses on microbial biofilms and their potential technological applications for sustainable development. It covers recent advances in biofilm technologies for contaminant remediation coupled to recovery of resources and serves as a complete reference on the science and technology behind biofilm mediated bioremediation and wastewater treatment"--